Enhancement of Thiamine Biosynthesis in Oil Palm Seedlings by Colonization of Endophytic Fungus Hendersonia toruloidea - Kamarudin, Amirah N.; Lai, Kok S.; Lamasudin, Dhilia U.; Idris, Abu S.; Balia Yusof, Zetty N. (Frontiers in Plant Science, 2017)
Thiamine, or vitamin B1 plays an indispensable role as a cofactor in crucial metabolic reactions including glycolysis, pentose phosphate pathway and the tricarboxylic acid cycle in all living organisms. Thiamine has been shown to play a role in plant adaptation towards biotic and abiotic stresses. The modulation of thiamine biosynthetic genes in oil palm seedlings was evaluated in response to root colonization by endophytic Hendersonia toruloidea. Seven-month-old oil palm seedlings were inoculated with H. toruloidea and microscopic analyses were performed to visualize the localization of endophytic H. toruloidea in oil palm roots. Transmission electron microscopy confirmed that H. toruloidea colonized cortical cells. The expression of thiamine biosynthetic genes and accumulation of total thiamine in oil palm seedlings were also evaluated. Quantitative real-time PCR was performed to measure transcript abundances of four key thiamine biosynthesis genes (THI4, THIC, TH1, and TPK) on days 1, 7, 15, and 30 in response to H. toruloidea colonization. The results showed an increase of up to 12-fold in the expression of all gene transcripts on day 1 post-inoculation. On days 7, 15, and 30 post-inoculation, the relative expression levels of these genes were shown to be downregulated. Thiamine accumulation was observed on day 7 post-colonization and subsequently decreased until day 30. This work provides the first evidence for the enhancement of thiamine biosynthesis by endophytic colonization in oil palm seedlings.